2021
DOI: 10.1186/s12935-021-02002-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DDIT4 and TPTEP1 are associated with metastasis and advanced stages in colorectal cancer patients: a study utilizing bioinformatics prediction and experimental validation

Abstract: Background Various diagnostic and prognostic tools exist in colorectal cancer (CRC) due to multiple genetic and epigenetic alterations causing the disease. Today, the expression of RNAs is being used as prognostic markers for cancer. Methods In the current study, various dysregulated RNAs in CRC were identified via bioinformatics prediction. Expression of several of these RNAs were measured by RT-qPCR in 48 tissues from CRC patients as well as in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 99 publications
3
6
0
Order By: Relevance
“…In this respect, eight mRNAs (SLC4A4, MMP1, MMP3, GCG, CXCL1, CXCL3, CLCA1, and CLCA4), three lncRNAs (UCA1, LINC00449, TPT3P1) and four miRNAs (has-miR-1301, has-miR-132, has-miR-339, has-miR-497) were found to be significantly (p < 0.01) related with poor OS of CRC patients. A majority of these hub genes were recently investigated as potential prognostic biomarkers, bioinformatically and experimentally [62][63][64][65]. Moreover, in our multivariate Cox model, our results suggested that out of four final lncRNAs, LINC00974 was the only lncRNA shown as a novel and potential predictor of DFS in patients with CRC, which is also reported by Gao et al in gastric carcinoma [66].…”
Section: Discussionsupporting
confidence: 83%
“…In this respect, eight mRNAs (SLC4A4, MMP1, MMP3, GCG, CXCL1, CXCL3, CLCA1, and CLCA4), three lncRNAs (UCA1, LINC00449, TPT3P1) and four miRNAs (has-miR-1301, has-miR-132, has-miR-339, has-miR-497) were found to be significantly (p < 0.01) related with poor OS of CRC patients. A majority of these hub genes were recently investigated as potential prognostic biomarkers, bioinformatically and experimentally [62][63][64][65]. Moreover, in our multivariate Cox model, our results suggested that out of four final lncRNAs, LINC00974 was the only lncRNA shown as a novel and potential predictor of DFS in patients with CRC, which is also reported by Gao et al in gastric carcinoma [66].…”
Section: Discussionsupporting
confidence: 83%
“…The relative quantity was calculated by the 2 -△ △ Ct method. The results for miRNA were normalized to U6 snRNA, and the results for DDIT4 were normalized to GAPDH (22). The primers are listed in Table 1 (14,22).…”
Section: Reverse Transcription Quantitative Polymerase Chain Reaction...mentioning
confidence: 99%
“…The expression levels of DDIT4 and SULF1 were significantly positively correlated with TPTEP1, and significantly negatively correlated with miR-148b-3p. According to the predicted binding site, these correlations may be explained by mRNA-miRNA network ( 70 ).…”
Section: Research Progress On Lncrnas That Participate In the Regulat...mentioning
confidence: 99%